The Effect of Different Probiotic Sources on Vannamei Shrimp (Litopenaeus vannamei) Cultivation with Biofloc System - Ardana Kurniaji; Diana Putri Renitasari; Siti Aisyah Saridu; Anton Anton; Yunarty Yunarty (Journal of Aquaculture and Fish Health, 2023)
An important component in the application of biofloc is the presence of probiotic bacteria as a floc-forming agent. This study aimed to analyze the differences in the yield of vannamei shrimp in a biofloc system using commercial probiotics and independent probiotics on a laboratory scale. The study design was a completely randomized design with 3 treatments and 4 replications, including independent probiotics (IP), commercial probiotics (CP) and control (C). PM utilized an independent formula with starter bacteria Lactobacillus casei and PK contained bacteria Bacillus sp., Pseudomonas sp., Nitrosomonas sp., Aerobacter sp., Nitrobacter sp. Probiotics were fermented 24 hours before its application to the maintenance medium. A total of 15 shrimp/aquarium measuring 3.29 ± 0.48 g were reared for 27 days after the floc was first formed. The results showed that the growth and feed conversion ratio of vannamei shrimp in the biofloc system were higher than that of the control (P<0.05). Growth and feed conversion ratio between probiotic treatments did not show significantly different results (P>0.05). Survival in treatment and control groups was not significantly different (P>0.05). The observed floc volumes which increased during the rearing of vannamei shrimp were up to 6.50-7.50 mL/L. Several types of organisms found in the flock included nematodes, phytoplankton, copepods and protozoa. The observed water quality was the same in each treatment except for higher dissolved oxygen and ammonia in the control. This study recommends the use of independent probiotics in vannamei shrimp culture based on biofloc technology.